Evaluation of the Addition of Supplement Wafers Containing Prill Fat to Sheep Fed Complete Feed In Vitro - Saputra, Andhio; Retnani, Yuli; Diapari, Didid (Faculty of Animal Science, Universitas Brawijaya, 2025)
The addition of wafers to animal feed has shown potential for improving feed quality and digestive efficiency in sheep. This study evaluated the effects of different wafer supplementation levels—0.0393 g of wafer (T1), 0.0786 g of wafer (T2), and 0.1179 g of wafer (T3)—on feed quality, rumen fermentability, and nutrient digestibility. A completely randomized design with four treatments and three replicates was used, and parameters such as the rumen pH, ammonia (NH?) concentration, total volatile fatty acid (VFA) content, dry matter digestibility (DMD), and organic matter digestibility (OMD) were measured. Statistical analysis via ANOVA followed by Duncan's test revealed that the addition of wafers significantly increased the DMD and OMD, with values increasing from 73.45 ± 0.59% and 73.11 ± 0.67% at T0 to 81.75 ± 1.14% and 81.26 ± 1.23% at T3, respectively. The NH? concentration increased from 11.80 ± 0.27 mM at T0 to 16.48 ± 0.24 mM at T3, whereas the VFA concentration increased from 82.38 ± 1.92 mM to 147.55 ± 3.67 mM during the same treatment period. These increases indicate improved fermentation activity and more efficient nutrient utilization due to the addition of wafers. Although the DMD and OMD values were higher than those reported in previous studies, this may indicate more efficient feed degradation and better energy release, thereby supporting improved livestock performance. Overall, the addition of 0.1179 g of wafer (T3) yielded the best results, confirming the effectiveness of wafer supplementation in improving feed quality and rumen function in rams.